Abnormal larval neuromuscular junction morphology and physiology in Drosophila prickle isoform mutants with known axonal transport defects and adult seizure behavior. (3rd July 2022) - Ueda, Atsushi; O'Harrow, Tristan C. D. G.; Xing, Xiaomin; Ehaideb, Salleh; Manak, J. Robert; Wu, Chun-Fang
Abstract: Previous studies have demonstrated the striking mutational effects of the Drosophila planar cell polarity gene prickle (pk) on larval motor axon microtubule-mediated vesicular transport and on adult epileptic behavior associated with neuronal circuit hyperexcitability. Mutant alleles of the prickle - prickle ( pk pk ) and prickle - spiny-legs ( pk sple ) isoforms (hereafter referred to as pk and sple alleles, respectively) exhibit differential phenotypes. While both pk and sple affect larval motor axon transport, only sple confers motor circuit and behavior hyperexcitability. However, mutations in the two isoforms apparently counteract to ameliorate adult motor circuit and behavioral hyperexcitability in heteroallelic pk pk /pk spl e flies. We have further investigated the consequences of altered axonal transport in the development and function of the larval neuromuscular junction (NMJ). We uncovered robust dominant phenotypes in both pk and sple alleles, including synaptic terminal overgrowth (as revealed by anti-HRP and -Dlg immunostaining) and poor vesicle release synchronicity (as indicated by synaptic bouton focal recording). However, we observed recessive alteration of synaptic transmission only in pk/pk larvae, i.e. increased excitatory junctional potential (EJP) amplitude in pk/pk but not in pk /+ or sple / sple . Interestingly, for motor terminal excitability sustained by presynaptic Ca 2+ channels, both pk and sple exerted strong effects to produce prolonged depolarization. Notably, only sple acted dominantly whereas pk /+ appeared normal, but was able to suppress the sple phenotypes, i.e. pk/sple appeared normal. Our observations contrast the differential roles of the pk and sple isoforms and highlight their distinct, variable phenotypic expression in the various structural and functional aspects of the larval NMJ.